The Effect of Parenting and The Effectiveness of Learning Videos on Independence In Self-Building Skills of Mentally Retarded Children - Widyarini, Ajeng; Jannah, Artha Roichatul (Universitas Negeri Surabaya, 2025)
Children with mental retardation have difficulty developing independence in self-help skills. Independence in self-help skills is a very important aspect in the development of mentally retarded children, because the ability to be independent in self-help can help improve the quality of life and function of children in the surrounding environment. The provision of appropriate parenting by parents can be believed to have a significant impact on the development of children's independence. The purpose of this research is to explore parents' views on the concept of parenting applied and its influence on the independence of children's self-help skills, and parents' views on providing learning videos to train children's self-help independence. This study uses a qualitative approach using in-depth interview methods, the research subjects consisted of 10 parents who have mentally retarded children. The findings of this study indicate that proper parenting can support children's emotional development in the aspect of self-help independence, and with the existence of learning videos, it is possible to help train direct practice of self-help with a note that it remains under the supervision of parents. The parenting provided by parents can provide a balance between tenderness and discipline that can affect the independence of self-help, this study emphasizes that it is very important the role of parents in teaching self-help skills to fully support positive development in children. Keywords: Parenting, Self-help, Mental Retardation, Learning Video